2014
DOI: 10.3906/sag-1304-141
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of sclerosing angiomatoid nodular transformation: radiological and histopathological analyses

Abstract: This paper investigates steady state solutions to thermally radiating and chemically reactive fluid in a channel. The reaction is assumed to be strongly exothermic under generalized Arrhenius kinetics, neglecting the consumption of the material. Approximate analytical solutions are constructed for the governing nonlinear boundary value problem using WKBJ approximation. Results pertaining to 4 categories of mass species propagation parameter are derived. Two special reactions are used in the validation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…In the remaining patients, the main symptom was abdominal pain ( n = 39). Other symptoms were a palpable abdominal mass, cytopenias, flank pain, pelvic pain, fever, nosebleed and anemia [ 6 , 7 ], vomiting, pruritus in the lower limbs [ 8 ], and weight loss [ 9 ]. There were two reported deaths in the Martel's cases [ 1 ]: a 56-year-old woman who died of disseminated lung adenocarcinoma and a 46-year-old man with concurrent bronchogenic squamous cell carcinoma who died of sepsis post splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining patients, the main symptom was abdominal pain ( n = 39). Other symptoms were a palpable abdominal mass, cytopenias, flank pain, pelvic pain, fever, nosebleed and anemia [ 6 , 7 ], vomiting, pruritus in the lower limbs [ 8 ], and weight loss [ 9 ]. There were two reported deaths in the Martel's cases [ 1 ]: a 56-year-old woman who died of disseminated lung adenocarcinoma and a 46-year-old man with concurrent bronchogenic squamous cell carcinoma who died of sepsis post splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The weight of splenectomy specimens in the literature varies from 68 to 2720 g, most cases being recorded after total splenectomy. During operation or macroscopic examination, certain signs may be visible; particularly, the mass appears as multiple individual and confluent nodules with sizes ranging from 1.2 to 17 cm (median size:5.2 cm), well-circumscribed, non-encapsulated, a bosselated mass with multiple dark brown nodules (bleed areas in angiomatoid nodules) interspersed with fibrotic stroma [ 24 , [37] , [38] , [39] , [40] ]. In the literature, most authors (>95%) reported multiple nodules and fibrotic stroma or scars [ 2 , 20 , [40] , [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 230 SANT patients undergoing laparoscopic, open splenectomy or biopsy between 2004 and April 2020 were reported on in English language literature [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. Patient information was only retrieved from English language medical databases with full-texts, using Google Scholar, PubMed, Scopus and Research-gate.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Macroscopically, on the cross-section of the spleen, the change has a starry aspect. In a large number of reports, the starry shape of SANT has the "spoked wheel" appearance in MDCT and T2weighted MRI images [18,19,20]. However, characteristic and pathognomic radiological findings, which could help unequivocally diagnose SANT, have not been defined yet.…”
Section: Discussionmentioning
confidence: 99%